2017
DOI: 10.1021/jacs.7b02512
|View full text |Cite
|
Sign up to set email alerts
|

P–N Cooperative Borane Activation and Catalytic Hydroboration by a Distorted Phosphorous Triamide Platform

Abstract: Studies on the stoichiometric and catalytic reactivity of a geometrically constrained phosphorous triamide 1 with pinacolborane (HBpin) are reported. The addition of HBpin to phosphorous triamide 1 results in cleavage of the B-H bond of pinacolborane through addition across electrophilic phosphorus and nucleophilic N-methylanilide sites in a cooperative fashion. The kinetics of this process of were investigated by NMR spectroscopy, with the determined overall second order empirical rate law given by ν = − k[1]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
95
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(98 citation statements)
references
References 65 publications
3
95
0
Order By: Relevance
“…[9][10][11][12][13][14] As a result, innumerable procedures have been evolved to accomplish the addition of boranes to nitriles. All these procedures require more or less effective catalysts based on transition-metal complexes such as Co, Fe, Ru, [15][16][17][18][19][20][21][22][23] alkaline earth metal (Mg), [24][25][26][27][28][29][30][31][32][33][34][35] but the processes culminate in frustrated Lewis pairs. [36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] As a result, innumerable procedures have been evolved to accomplish the addition of boranes to nitriles. All these procedures require more or less effective catalysts based on transition-metal complexes such as Co, Fe, Ru, [15][16][17][18][19][20][21][22][23] alkaline earth metal (Mg), [24][25][26][27][28][29][30][31][32][33][34][35] but the processes culminate in frustrated Lewis pairs. [36][37][38] On the other hand, while the reduction of aryl and alkyl nitriles can be achieved using stoichiometric quantities of maingroup reducing agents such as LiAlH 4 and NaBH 4 , [39] the combustible nature of these reagents and large quantities of inorganic waste by-products they generate render the process unattractive, and hence reductive hydroboration is preferable in order to provide further functionality to the resultant amine.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we have shown that nontrigonal s 3 -P compounds (see 1 and 2,F igure 1a)e volve to pentacoordinate phosphorus (s 5 -P) products through oxidative addition of EÀHb onds (E = OR, NHR, Ru), [25][26][27][28] in some cases reversibly. [29][30][31][32][33][34][35] Although applications of the biphilic character of nontrigonal s 3 -P compounds such as 1 and 2 have emerged in reactivity,adirect experimental demonstration of how the C 3v !C s structural deformation controls s 3 -P frontier orbital energies has not been previously presented. With av iew toward establishing arational schema for biphilic s 3 -P design, we provide here the first explicit spectroscopic evidence validating the descent-in-symmetry hypothesis of biphilicity at s 3 -P.T hrough phosphorus K-edge X-ray absorption nearedge structure (XANES) spectroscopy and supporting (TD)DFT demonstrations,w eq uantify the impact of nontrigonal distortion (C 3v !C s !C 2v )onthe electronic structure of as eries of compositionally related compounds and show that nontrigonal s 3 -P compounds present inherently contracted frontier orbital energy gaps that colocalize electrondonor and electron-acceptor behavior at as ingle s 3 -P site, engendering biphilic character.O verall, these results codify how structural modifications control s 3 -P electronic structure and provide aforward-looking blueprint for the development of next-generation nontrigonal P III catalysts and ligands with exceptional biphilic reactivity.…”
mentioning
confidence: 99%
“…Tethered triamido ligands have recently been applied to achieve nonclassical geometries and reactivity paradigms at B III and P III centres . In the P III case, Radosevich and co‐workers found that the ground state is a distorted‐pyramidal 8‐P‐3 geometry that undergoes unusually facile inversion at phosphorus because of the availability of a transient 10‐P‐3 intermediate along the inversion coordinate (Scheme d) ,. However, despite its purported importance in unlocking a wide range of valuable reactivity, a planar 10‐E‐3 intermediate has never been experimentally realized for any group 15 triamide, further motivating our quest for a 10‐Bi‐3 environment within the (R)N‐N‐N(R) framework.…”
Section: Methodsmentioning
confidence: 99%